2018
DOI: 10.1136/bmjgh-2018-000794
|View full text |Cite
|
Sign up to set email alerts
|

Variation in cost and performance of routine immunisation service delivery in India

Abstract: A comprehensive understanding of the costs of routine vaccine delivery is essential for planning, budgeting and sustaining India’s Universal Immunisation Programme. India currently allocates approximately US$25 per child for vaccines and operational costs. This budget is prepared based on historical expenditure data as information on cost is not available. This study estimated the cost of routine immunisation services based on a stratified, random sample of 255 public health facilities from 24 districts across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 8 publications
1
33
0
Order By: Relevance
“…These results also report the early effects of the program, whereas our analysis adds more recent data. 4 Finally, a recent work by Chatterjee et al (2018) found a positive impact of JSY on immunization in India, though the data used and methodology are different from this paper.…”
Section: Previous Research On the Impacts Of Jsymentioning
confidence: 62%
See 1 more Smart Citation
“…These results also report the early effects of the program, whereas our analysis adds more recent data. 4 Finally, a recent work by Chatterjee et al (2018) found a positive impact of JSY on immunization in India, though the data used and methodology are different from this paper.…”
Section: Previous Research On the Impacts Of Jsymentioning
confidence: 62%
“…Vaccines are inexpensive in India, and the actual cost to families for vaccination is small or zero meaning that institutional and informational barriers are more likely to prevent vaccination than cost barriers. According to one estimate, as of 2017, the cost of each dose of Bacillus Calmette-Guérin (BCG) cost around Rs 3.25 ($0.05), Rs 2.6 ($0.04), and Rs 32.5 ($.5), respectively, whereas the central government allocates approximately US$25 (Rs 1,625) per child for vaccines and operational costs (Chatterjee et al, 2018). Together, we expect a priori that exposure to the JSY will increase vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Funding for India's national immunization program remains inadequate. During 2013–2017, the estimated annual budgetary shortfall for the program increased from $8.6 to $544.2 million (in 2013 US$), primarily because of the introduction of pentavalent and other new vaccines …”
Section: Discussionmentioning
confidence: 99%
“…We estimated the maximum cost of such a vaccination programme at the lowest WTP threshold to be $21B (UI 16–27) and $15B (UI 12–19) in India and China, respectively, for three vaccination campaigns in 2027, 2037 and 2047. In comparison, annual universal infant vaccination programmes in India and China are estimated to cost approximately $700 million (2013–14 levels, adjusted to 2017 prices) [ 27 ] and $1B (2015 levels) [ 28 ], respectively, while the World Health Organization estimates the total annual budgets available for national strategic plans for tuberculosis in India and China at $583 million and $719 million in 2019, respectively. In this context, targeted vaccination may represent a more affordable approach.…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that an all-age adult and adolescent mass tuberculosis vaccination programme, considered cost-effective at country-specific cost-effectiveness thresholds, would impose a substantial budgetary burden on the health system in India and China. We estimated the maximum cost of such a vaccination programme at the lowest WTP threshold to be $21B (UI [16][17][18][19][20][21][22][23][24][25][26][27] and $15B (UI [12][13][14][15][16][17][18][19] in India and China, respectively, for three vaccination campaigns in 2027, 2037 and 2047. In comparison, annual universal infant vaccination programmes in India and China are estimated to cost approximately $700 million (2013-14 levels, adjusted to 2017 prices) [27] and $1B (2015 levels) [28], respectively, while the World Health Organization estimates the total annual budgets available for national strategic plans for tuberculosis in India and China at $583 million and $719 million in 2019, respectively.…”
Section: In Contextmentioning
confidence: 99%